2014
DOI: 10.3892/or.2014.3508
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-specific protease 22-induced autophagy is correlated with poor prognosis of pancreatic cancer

Abstract: Abstract. Ubiquitin-specific protease 22 (USP22) is a component of the transcription regulatory histone acetylation complex SAGA, which broadly regulates gene transcription and correlates with cancer progression, metastasis and prognosis. Autophagy is a cell pathway with dual functions that promotes cell survival or death. However, it is not known whether USP22 can regulate autophagy in pancreatic cancer. In the present study, we first identified that USP22 was overexpressed in a large number of pancreatic can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…Several reports indicate that USP22 overexpression is linked to unfavorable outcomes in multiple types of cancers (He et al, 2015; Liang et al, 2014; Ning et al, 2012; Zhang et al, 2011). However, the mechanisms underlying USP22 overexpression in different malignancies and molecular links between histone deubiquitination and aggressive tumor growth are still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports indicate that USP22 overexpression is linked to unfavorable outcomes in multiple types of cancers (He et al, 2015; Liang et al, 2014; Ning et al, 2012; Zhang et al, 2011). However, the mechanisms underlying USP22 overexpression in different malignancies and molecular links between histone deubiquitination and aggressive tumor growth are still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…All studies were performed exclusively in patients from China. Seven of the studies were of patients with digestive system cancers (colorectal cancer, hepatocellular cancer, esophageal cancer, gastric cancer, and pancreatic cancer), 16 , 18 , 23 , 28 31 two of the studies were of patients with salivary carcinoma, 20 , 22 and seven of the studies were of patients with other cancer types (oral squamous cell carcinoma, lung cancer, glioma cancer, breast cancer, epithelial ovarian cancer, and papillary thyroid carcinoma). 17 , 19 , 21 , 32 35 IHC was the main method used to detect USP22 expression in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies reported that overexpression of USP22 may be involved in the drug resistance of cancer through a variety of mechanisms. Our published research has demonstrated that USP22 was related to the chemotherapy resistance to gemcitabine in pancreatic cancer (Liang et al, 2014). A recent study suggested that cisplatin can suppress the expression of USP22 through p38/MAPK pathway in HeLa cells (Ding et al, 2014).…”
Section: Discussionmentioning
confidence: 99%